2015
DOI: 10.1186/s40942-015-0021-8
|View full text |Cite
|
Sign up to set email alerts
|

Metamizole versus placebo for panretinal photocoagulation pain control: a prospective double-masked randomized controlled study

Abstract: BackgroundDiabetic retinopathy is one of most common and threatening ocular diseases. Many of these patients need to be submitted to panretinal photocoagulation (PRP), experiencing a significant level of pain. The purpose of this study is to evaluate the effectiveness of oral metamizole in reducing pain during PRP in patients with proliferative diabetic retinopathy (PDR) and very severe non-proliferative diabetic retinopathy (VSNDR).MethodsPatients from a single center with PDR or VSNDR and indication of bilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
7
1
Order By: Relevance
“…Acute procedural pain is still a neglected phenomenon in health care (Cakmak et al, 2017;Lee, 2016;Song et al, 2018), particularly in ophthalmic procedures (Araújo et al, 2015;Castro et al, 2014;Chen et al, 2012;Chiu & Wu, 2011;Quigley et al, 2019;Ramezani et al, 2017;Santo et al, 2016). These findings corroborate our results, since most of the patients who underwent argon LRP reported pain, despite the anesthetic used, which demonstrates the nociceptive nature of the procedure.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Acute procedural pain is still a neglected phenomenon in health care (Cakmak et al, 2017;Lee, 2016;Song et al, 2018), particularly in ophthalmic procedures (Araújo et al, 2015;Castro et al, 2014;Chen et al, 2012;Chiu & Wu, 2011;Quigley et al, 2019;Ramezani et al, 2017;Santo et al, 2016). These findings corroborate our results, since most of the patients who underwent argon LRP reported pain, despite the anesthetic used, which demonstrates the nociceptive nature of the procedure.…”
Section: Discussionsupporting
confidence: 87%
“…In order for the analyses to be comparable, the technique to encircle the posterior pole of the retina (around the vascular arches) was standardized. The LRP technique in our test was standardized for bias reduction and was based on previous studies that showed no significant difference in the presence of pain in relation to the power of the laser shots provided (Araújo et al, 2015;Castro et al, 2014;Chiu & Wu, 2011;Ko, Shim, Lee, & Cho, 2009;Ramezani et al, 2017;Richardson & Waterman, 2009).…”
Section: Laser Retinal Photocoagulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings in our study are contrary to the findings of some other studies evaluating the efficacy of COX-3 inhibitors on the rates of PIPP in comparison with control groups. In patients undergoing panretinal photocoagulation, intravenous infusion of 1 g of metamizole 40 min before the induction of GA resulted in a statistically significant reduction in pain perception associated with the procedure in comparison to the placebo control group [ 70 ]. The analgesic potencies of intravenous PA using paracetamol and metamizole at a dose of 1 g proved their similar efficacies for postoperative analgesia after retinal surgery in comparison to the control group [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted at Ophthalmology Service of the Hospital das Clínicas University of São Paulo Medical School by Rafael Barbosa de Araújo et al They concluded that the use of 1000 mg of Metamizole 40 minutes before PRP significantly reduced pain associated with the procedure in patients with PDR. 15 Similarly, Hazem et al in their study reported lower degree of pain associated with a better hemodynamic response in patients given 150 mg Pregabalin before photocoagulation. 16 The laser energy is focused on the retinal tissue and is absorbed by the underlying retinal pigment epithelium (RPE) and choroid.…”
Section: Discussionmentioning
confidence: 84%